Recent Advances in the Discovery and Development of Marine Microbial Natural Products - Xiong, Zhi-Qiang (MDPI, 2013)
Marine microbial natural products (MMNPs) have attracted increasing attention from microbiologists, taxonomists, ecologists, agronomists, chemists and evolutionary biologists during the last few decades. Numerous studies have indicated that diverse marine microbes appear to have the capacity to produce an impressive array of MMNPs exhibiting a wide variety of biological activities such as antimicrobial, anti-tumor, anti-inflammatory and anti-cardiovascular agents. Marine microorganisms represent an underexplored reservoir for the discovery of MMNPs with unique scaffolds and for exploitation in the pharmaceutical and agricultural industries. This review focuses on MMNPs discovery and development over the past decades, including innovative isolation and culture methods, strategies for discovering novel MMNPs via routine screenings, metagenomics, genomics, combinatorial biosynthesis, and synthetic biology. The potential problems and future directions for exploring MMNPs are also discussed.